Apoptosis of Lewis Lung Carcinoma Cells Induced by Microwave via p53 and Proapoptotic Proteins In vivo - Kou-Dong Zhang; Lin-Rong Tong; Shui-Ming Wang; Rui-Yun Peng; Hai-Dong Huang; Yu-Chao Dong; Xing-Xing Zhang; Qiang Li; Chong Bai (Chinese Medical Journal, 2017)
Background: Microwave therapy is a minimal invasive procedure and has been employed in clinical practice for the treatment of various types of cancers. However, its therapeutic application in non-small-cell lung cancer and the underlying mechanism remains to be investigated. This study aimed to investigate its effect on Lewis lung carcinoma (LLC) tumor in vivo. Methods: Fifty LLC tumor-bearing C57BL/6 mice were adopted to assess the effect of microwave radiation on the growth and apoptosis of LLC tumor in vivo. These mice were randomly assigned to 10 groups with 5 mice in each group. Five groups were treated by single pulse microwave at different doses for different time, and the other five groups were radiated by multiple-pulse treatment of a single dose. Apoptosis of cancer cells was determined by terminal deoxynucleotidyl transferase dUTP nick-end labeling assay. Western blotting was applied to detect the expression of proteins. Results: Single pulse of microwave radiation for 5 min had little effect on the mice. Only 15-min microwave radiation at 30 mW/cm2 significantly increased the mice body temperature (2.20 ± 0.82)°C as compared with the other groups (0.78 ± 0.29 °C, 1.24 ± 0.52 °C, 0.78 ± 0.42 °C, respectively), but it did not affect the apoptosis of LLC tumor cells significantly. Continous microwave radiation exposure, single dose microwave radiation once per day for up to seven days, inhibited cell division and induced apoptosis of LLC tumor cells in a dose- and duration-dependent manner. It upregulated the protein levels of p53, Caspase 3, Bax and downregulated Bcl-2 protein. Conclusions: Multiple exposures of LLC-bearing mice to microwave radiation effectively induced tumor cell apoptosis at least partly by upregulating proapoptotic proteins and downregulating antiapoptotic proteins. Continuous radiation at low microwave intensity for a short time per day is promising in treating non-small-cell lung cancer.